Cytotoxic sesquiterpene lactones from Artemisia anomala. (June 2017) - Li, Lu; Liu, Hongchun; Tang, Chunping; Yao, Sheng; Ke, Changqiang; Xu, Chenghui; Ye, Yang
Graphical abstract: Highlights: Two new sesquiterpene lactones along with six known analogs were isolated from A. anomala . Their structures were determined on the basis of extensive spectroscopic analyses. All compounds have been evaluated for their in vitro cytotoxicity. Compounds6 and7 showed moderate inhibition against human cancer cell lines HepG2 and A549. Abstract: Two new sesquiterpene lactones, 8 α -acetoxy-1, 10 α -epoxy-2-oxo-guaia-3, 11(13)-dien-12, 6 α -olide (1 ) and 13-acetoxy-1-oxo-4 α -hydroxy-eudesman-2(11)-dien-12, 6 α- olide (2 ), along with six known analogs (3 -8 ), were isolated from the whole plant of Artemisia anomala S. Moore. Their structures were elucidated by extensive analysis of spectroscopic data. Compounds6 and7 exhibited in vitro moderate cytotoxicity against A549 cells with IC50 values of 0.6 and 0.9  μ M, and HepG2 cells with IC50 values of 5.4 and 3.0  μ M, respectively.